Regulation of tillage on grain matter accumulation in maize - Wang, Li-Qing; Yu, Xiao-Fang; Gao, Ju-Lin; Ma, Da-Ling; Liu, Hong-Yue; Hu, Shu-Ping (Frontiers in Plant Science, 2024)
Introduction To address issues related to shallow soil tillage, low soil nutrient content, and single tillage method in maize production in the Western Inner Mongolia Region, this study implemented various tillage and straw return techniques, including strip cultivation, subsoiling, deep tillage, no-tillage, straw incorporation with strip cultivation, straw incorporation with subsoiling, straw incorporation with deep tillage, and straw incorporation with no tillage, while using conventional shallow spinning by farmers as the control. Methods We employed Xianyu 696 (XY696) and Ximeng 6 (XM6) as experimental materials to assess maize 100-grains weight, grain filling rate parameters, and grain nutrient quality. This investigation aimed to elucidate how tillage and straw return influence the accumulation of grain material in different maize varieties. Results and discussion The results indicated that proper implementation of tillage and straw return had a significant impact on the 100-grains weight of both varieties. In comparison to CK (farmer’s rotary rotation), the most notable rise in 100-grains weight was observed under the DPR treatment (straw incorporation with deep tillage), with a maximum increase of 4.84% for XY696 and 6.28% for XM6. The proper implementation of tillage and straw return in the field resulted in discernible differences in the stages of improving the grain filling rates of different maize varieties. Specifically, XY696 showed a predominant increase in the filling rate during the early stage (V1), while XM6 exhibited an increase in the filling rates during the middle and late stages (V2 and V3). In comparison to CK, V1 increased by 1.54% to 27.56% in XY696, and V2 and V3 increased by 0.41% to 10.42% in XM6 under various tillage and straw return practices. The proper implementation of tillage and straw return had a significant impact on the nutritional quality of the grains in each variety. In comparison to CK, the DPR treatment resulted in the most pronounced decrease in the soluble sugar content of grains by 25.43% and the greatest increase in the crude fat content of grains by 9.67%. Conclusion Ultimately, the proper implementation of soil tillage and straw return facilitated an increase in grain crude fat content and significantly boosted grain weight by improving the grouting rate parameters at all stages for various maize varieties. Additionally, the utilization of DPR treatment proved to be more effective. Overall, DPR is the most promising strategy to improve maize yield and the nutritional quality of grain in the long term in the Western Inner Mongolia Region.